The Use of First Language in the Second-Language Classroom: A Support for Second Language Acquisition (GIST – Education and Learning Research Journal, 2014)
This action research project was carried out in order to identify the role of first language in the second-language classroom. This study was conducted in a Colombian international school with an English immersion program for kindergarten students attending their first year of school. The purpose of this study was to identify if the use of the mother tongue in the classroom increases comprehension and facilitates the second language acquisition process. Two lesson plans were designed: the first one using only English as the language of instruction, and the second one using both languages, Spanish and English. The results demonstrate that students do benefit from the use of the first language in the classroom, transferring concepts from their mother tongue to the new language.
Keywords: Second language acquisition; language transfer; first language acquisition; language of instruction